A multicast photonic switching network - Suliman, F. M.; Mohammad, Abu Bakar; Seman, K. (2002)
A multicast photonic switching network is proposed. The switch is a space division multistage network using 2Ã—2 optical switching elements. The idea behind the proposed architecture and a recursive definition for it are presented. Some properties of the switch are derived and analyzed. The performance of the switch is also discussed and and compared with other designs.